1994
DOI: 10.1046/j.1365-2648.1994.20010167.x
|View full text |Cite
|
Sign up to set email alerts
|

The role of the health visitor in identifying and working with vulnerable families in relation to child protection: a review of the literature

Abstract: This paper presents an overview of the research surrounding the role of the health visitor in identifying and working with vulnerable families in relation to child protection. Only a limited number of empirical studies have been completed within the field of health visiting, so this review draws on most of the literature published over the last 15 years, which is mainly British in origin. No previous reviews have focused on this specific area of health visiting. Clearly with the recent increase in public and o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
9
0
2

Year Published

1998
1998
2008
2008

Publication Types

Select...
4
2
2

Relationship

0
8

Authors

Journals

citations
Cited by 19 publications
(11 citation statements)
references
References 10 publications
0
9
0
2
Order By: Relevance
“…There are however far fewer reports of how best to target the delivery of these interventions effectively towards those families who could gain most from them, and most of these have been based on simple demographics -for example Olds' seminal work on intensive home visitation was aimed at a target group of mothers who were in their teens, unmarried or living in deprived areas (Olds et al 1998b). Guidelines, such as those developed for children who may require statutory child protection measures, appear to offer a slightly more sophisticated approach -but they may have limited value in practice (Appleton et al 2004;Appleton 1994b). It is, moreover, unlikely that simple guidelines could ever form the sole basis of complex judgements about families who may benefit from more subtle types of intervention.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…There are however far fewer reports of how best to target the delivery of these interventions effectively towards those families who could gain most from them, and most of these have been based on simple demographics -for example Olds' seminal work on intensive home visitation was aimed at a target group of mothers who were in their teens, unmarried or living in deprived areas (Olds et al 1998b). Guidelines, such as those developed for children who may require statutory child protection measures, appear to offer a slightly more sophisticated approach -but they may have limited value in practice (Appleton et al 2004;Appleton 1994b). It is, moreover, unlikely that simple guidelines could ever form the sole basis of complex judgements about families who may benefit from more subtle types of intervention.…”
Section: Discussionmentioning
confidence: 99%
“…It is therefore surprising that there appears to be so little peer-reviewed literature on how HVs identify those families to which they potentially have most to offer.. While there are a number of reports on the role of health visitors in identifying children in need of statutory protection (Appleton 1994a;Appleton 1994b;Duncan 1992;Ling et al 2000) we have been unable to find any literature on how HVs identify, more subtle problems in the relationship between parents and children. This paper reports on how HVs in one large Scottish city identify difficulties in the early parent-child relationship…”
Section: Introductionmentioning
confidence: 99%
“…Luker & Chalmers (1990), Chalmers (1993) and Appleton (1994, 1996) have found that the tasks of gaining the confidence of families, of recognizing the clients’ real needs and of taking care of so‐called problem or high‐risk families are challenges in nursing. Nevertheless, the school nurse’s role in identifying child abusing families and in caring for them, instead of concentrating only on the child, is of central importance ( Appleton, 1994, 1996; Bekemeier, 1995). O’Toole et al .…”
Section: Discussionmentioning
confidence: 99%
“…It would appear that the increased visiting by the PHN in both of the above cases was of a ‘monitoring’ nature and explicit objectives in relation to the purpose of visiting outside of the prescribed times were not set out. Appleton (1994b) suggests that the reluctant monitoring role being played by the health visitor has come about as a result of the gap in the service. Given the extent of the remit of PHNs, the generalist nature of their work and their education and expertise in relation to tertiary child protection, the question must be asked as to what exactly the PHN can achieve in terms of meaningful intervention .…”
Section: Discussionmentioning
confidence: 99%